Kesiapan Tenaga Administrasi Sekolah Dalam Menghadapi Perubahan Organisasi Pada Masa Wabah Covid-19 di SMPN se Kabupaten Solok Selatan - Wisnu Adikarsa Hutomo; Rusdinal Rusdinal; Nurhizrah Gistituati; Ahmad Sabandi (Journal of Educational Administration and Leadership, 2022)
The study was conducted to obtain data and information regarding the readiness of school administration staff in dealing with organizational changes during the COVID-19 pandemic in terms of the accuracy of changes, confidence in their abilities, management support, and personal benefits. This research is descriptive quantitative. The population of school administration staff in this study amounted to 166 administrative staff. Therefore, this research sample was taken using the 4-level Cluster Sampling technique so that 35 school administrators were selected as samples. The research instrument is a semantic differential scale model questionnaire which has 7 alternative answers. The results of data analysis show that the readiness of school administrative staff in dealing with organizational changes during the COVID-19 outbreak at SMPNs in South Solok Regency is in the ready category with an achievement percentage of 74.29.